(untitled) (Jurnal Informatika dan Komputasi: Media Bahasan, Analisa dan Aplikasi, 2023)
One of the technological developments that is beneficial to humans is to minimize and assist human performance in controlling the house. Sometimes in the use and control of the house efficiency is still not maximized. The use of Arduino Uno is very diverse, namely it can be used to develop interactive objects, take input from various switches or sensors, control or control curtains, detect fires, and security at doors. At present, most of the household control systems still use human power, for example to open and close curtains, being oblivious to fire hazards, this makes human work slow and careless. Arduino Control in Organizations can help users control home conditions.